Bildverarbeitung für die Medizin 2025: Proceedings, German Conference on Medical Image Computing, Regensburg March 09-11, 2025 - Palm, Christoph; Breininger, Katharina; Deserno, Thomas M.; Handels, Heinz; Maier, Andreas; Maier-Hein, Klaus H.; Tolxdorff, Thomas M. (Springer Vieweg, 2025)
Keynote -- Session 1: Image Registration -- Session 2: Video Analysis -- Session 3: Shape Modelling -- Session 4: Generative Models -- Session 5: Improving Reliability -- Session 6: Ultrasound & OCT -- Session 7: Digital Pathology -- Session 8: Segmentation -- Postersession 1 -- Postersession 2.
Keywords: Konferenzschrift -- 09.03-11.03.2025 -- Regensburg